New Inequalities for Gamma and Digamma Functions - M. R. Farhangdoost; M. Kargar Dolatabadi (Journal of Applied Mathematics)
By using the mean value theorem and logarithmic convexity, we obtain some new inequalities for gamma and digamma functions.